Penerapan Metode Gost Untuk Mendeteksi Keaslian File Dokumen - Anggriani, Lia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Humans have the ability to be able to detect the authenticity of document files. This capability will be very useful when applied to machines such as computers. The purpose of this research is to implement the GOST algorithm (Gosudarstennyi Standard or often called the Government Standard. The gost method is a block cipher algorithm developed by a national of the USSR. GOST cryptography is a 64-bit block cipher with a key length of 256 bits. This algorithm iterates over the algorithm. simple encryption of 32 rounds (round), to encrypt the 64-bit plaintext first broken down into 32 bits on the left, L and 32 bits on the right R. Design is a process that aims to analyze, assess, improve, and compile a system, both physical and non-physical systems that are optimal for the future by utilizing existing information Design is the process of developing a new system specification based on analysis recommendations system.Application is a noisy program n commands to perform data processing. Application in general is a manual process that is informed to the computer by creating a system or program to make it more optimally efficient